A Comparison of the Positive Effects of Structured and Nonstructured Art Activities. Issue 1 (2nd January 2019) - Cross, Gemma; Brown, Patricia M.
Abstract: This study compared the effects of 2 art activities (structured and nonstructured) and a focused breathing exercise on outcome measures of mindfulness, anxiety, and affect. Seventy-seven participants, recruited from university students and the general public, were randomly assigned to either 15 min of coloring a mandala (structured), free drawing (nonstructured), or a focused breathing exercise. Results demonstrated that all 3 interventions produced significant improvements in the outcome measures at posttest compared with pretest. However, no significant differences were found across the 3 intervention conditions. These findings inform the design of brief interventions aimed at achieving short-term positive psychological benefits in nonclinical populations.